Energy Consumption and Foreign Direct Investment Inflows in Nigeria: An Empirical Perspective - Olaoye, Olusegun Peter; Aderemi, Timothy Ayomitunde; John, Nwagwu Chinedu; Jude-Okeke, Yvonne; Ezinwa, Azuh Dominic (International Journal of Energy Economics and Policy, 2020)
The aim of this study is to examine the relationship between energy consumption and foreign direct investment in Nigeria over the period of 1990 to 2017. Consequently, Data were collected from UNCTAD World Bank database, World Data Atlas and CBN Statistical Bulletin respectively. Cointegration, DOLS and Granger Causality approach were employed to address the objective of the study. The major findings in this study are summarized as follow. Energy consumption and FDI inflow have a significant negative relationship with each other. There is a significant positive relationship between energy consumption and oil exports. However, openness of the economy and energy consumption have a non-significant negative relationship. In the same vein, there is an existence of a unidirectional causality which runs from FDI to oil exports in Nigeria. There is one way causal relationship running from energy consumption to oil exports. FDI inflows Granger Causes energy consumption. Meanwhile, energy consumption Granger Causes openness of the economy. Due to the findings that emerged in this study, it is important that this study recommends the following to the policy makers in Nigeria since energy consumption does not drive FDI inflows the policy makers in the country should provide a conducive climate that will facilitate the accessibility of foreign investors to primary energy consumption in the country. Also, the country should improve the value addition to the production of primary energy so that its consumption could be competitive in the global market. Keywords: Energy; Consumption; FDI; Oil Exports and Nigeria JEL Classifications: F21, F23 DOI: https://doi.org/10.32479/ijeep.8489